THE EFFECTIVENESS OF ALBENA AND ALBENA IN COMBINATION WITH T AND B-ACTIVIN A IN EXPERIMENTAL DICTYOCAULUS LAMBS - T. Yu. Degtyarevskaya (Российский паразитологический журнал, 2016)
Objective of research. The aim of the research was to investigate the anthelmintic efficiency of Albena and Albena in combination with T and b-activin a in experimental dictyocaulus lambs. Materials and methods. Test Albena with 20 % of albendazole and Albena in combination with T and b-a activin is carried out at the experimental dictyocaulus lambs in August-September 2013 on 18 crossbred lambs aged 4-5 months, free from infection, as confirmed by the results coprevalence studies by the method of Berman and flotation. Lambs infected with invasive larvae of Dictyocaulus filaria at a dose of 1000 copies/goal. by providing them with water for oral administration. In 30 days after infection the lambs were divided into 3 equal groups of 6 animals each and were kept in machines under conditions that prevent spontaneous infection of lambs. Lambs of the first group was administered individually orally Albin in the form of 20% of granulated powder in a dose of 5 mg/kg DW of 0.25 g of granules per 10 kg of body weight. Animals of the second group asked Albin the same dose and subcutaneously T-activin in a dose of 2 mg/kg once a day for 1, 3 and 7 days and b-activin in a dose of 5 μg/kg intramuscularly once a day for 5 days. The third group of lambs was used and served as control. The efficacy of the drug was determined by helminthological autopsy of the lungs of lambs 15 days after deworming. Results and discussion. Obtained a 100% efficacy of treatment of lambs with Albena in combination with T and b-activin. Albin at a dose of 5 mg/kg showed 92,3% effective against D. filaria imaginal. Interenvironment lambs of the control group was 23.5±2,4 EKZ/goal.